Let f(x) = 4- 3x which of the following is equal to f’ (-1) a) -7 b) 7 c) -3 ...
Let f(x) = 4- 3x which of the following is equal to f’ (-1) a) -7 b) 7 c) -3 ...
I can't figure out how to get that pesky zero out of the denominator!
Find dy/dx by implicit differentiation : e^x/y = x - y
f(x) = sin(x), a=p/6
basic differentiation rules
(a) y= tan(sqrt 3t)
F(x) = 3-2x-4x^2 at x=2
Differentiate y = x/e^x
Differentiate H(u) = (u - sqrt(u)) (u + sqrt(u))
Find by implicit differentiation: x^2 + xy - y^2 = 4
g(x) = cosh(ln(x))
y = (2-v^2)/ (2 + v^2)
F9x) = 3-√x / 9-x that is continuous at a=9
Answer choices are: 1. f'(x) = 6 / (√x^2 − 7) 2. f'(x) = − 12 / (√x^2−7 ) 3. f'(x) = −3 / (√x^2−7) 4. f′(x) = 3 / (√x^2−7) 5. f'(x) = −6 / (√x^2−7) 6...
I know I need to use the chain rule but I never get the right answer when I try on this problem
(infinity symbol) ∑ (n^2)/(5n^2+4) n=1 How do you know if it diverges. Please explain step by step.
Differentiate f(x) = xe^x csc(x)
Would the answer just be rsintheta=rcostheta?
A concial tank with an upper radius of 4m and a height of 5m drains into a cylindrical tank with a radius of 4m and a height of 5m. If the water level in the conical tank drops at a rate of 0.5m/min,...
Differentiate f(x) = A/(B + Ce^x)